2015
DOI: 10.1038/srep09654
|View full text |Cite
|
Sign up to set email alerts
|

High aspect ratio 10-nm-scale nanoaperture arrays with template-guided metal dewetting

Abstract: We introduce an approach to fabricate ordered arrays of 10-nm-scale silica-filled apertures in a metal film without etching or liftoff. Using low temperature (<400°C) thermal dewetting of metal films guided by nano-patterned templates, apertures with aspect ratios up to 5:1 are demonstrated. Apertures form spontaneously during the thermal process without need for further processing. Although the phenomenon of dewetting has been well studied, this is the first demonstration of its use in the fabrication of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The disks may thus transform their shapes into thicker disks or spheres in a crystallographic phase transition process (Fig. 1c) 20,21 , and finally they may be ablated away. By the excitation of SPR with electric field confinement, light energy is redistributed and concentrated in specific regions of the disk-hole unit cell, enabling a fine tuning of the morphology by adjusting the input pulse energy density.…”
mentioning
confidence: 99%
“…The disks may thus transform their shapes into thicker disks or spheres in a crystallographic phase transition process (Fig. 1c) 20,21 , and finally they may be ablated away. By the excitation of SPR with electric field confinement, light energy is redistributed and concentrated in specific regions of the disk-hole unit cell, enabling a fine tuning of the morphology by adjusting the input pulse energy density.…”
mentioning
confidence: 99%
“…The gap was estimated to be ~280 nm in depth with an opening of only 9.2 nm in width. This aspect ratio is ~30 which is quite extraordinary for sub-10 nm patterns 34 . Figure 2d illustrates a tiny gap size on the Al 2 O 3 mask of a critical dimension as low as 2.9 nm after the subsequent ion exposure.…”
Section: Resultsmentioning
confidence: 94%
“…Gold was deposited on the template via electron-beam evaporation technique at room temperature. The metal dewetting was induced via thermal annealing at 400 °C (the melting point for Au nanoparticles with a radius larger than 10 nm is about 1000 °C) in a rapid thermal processor for 5–30 minutes 14 . The wetting angle between Au and Si with oxide layer is about 140° 56 .…”
Section: Resultsmentioning
confidence: 99%
“…The SSD technique has typically been used to fabricate nanodot arrays with diameter from tens to hundreds nanometers, which are important elements in a variety of nanodots-based applications, including high-density magnetic recording media 1 2 , solar cells 3 4 , catalysts for nanowire growth 5 6 , and many plasmonic devices, such as plasmon-resonance wave guides 7 8 , plasmon-enhanced photovoltaic devices 9 10 , plasmonic LEDs 11 12 , and biosensors 13 . Our recent work 14 showed that SSD can also be used to fabricate nano-aperture arrays with high yield and at low costs. The diameter of nano-aperture obtained by SSD can be controllable down to 10 nanometers with an aspect ratio of up to 1:5, which makes it a great candidate in the application of nanopore-based single molecule sensing 15 16 , x-ray diffraction 17 18 , and also plasmonic devices 19 20 .…”
mentioning
confidence: 99%